Modeling and projection of fish supply and demand in Malaysia, 2000-2020. - Tai, Shzee Yew; Mohd Noh, Kusairi; Omar, Ishak; Raja Abdullah, Nik Mustapha (Universiti Malaysia Sarawak, 2008)
The fishery sector in Malaysia is expected to play important roles in eradicating poverty, increasing food security and helping to reverse the deficit food trade balance. In the Third Malaysian National Agriculture Policy Plan, the production target for the sector is to increase from 1.45 million mt in 2000 to two million mt by 2010. Adapting from the AsiaFish model, a disaggregated fish supply and demand model for Malaysia is constructed to analyse whether the fishery sector can live up to the expectations. The model consists of the producer, consumer and trade cores as well as the model closure equation. It is used to project fish supply, demand and trade in Malaysia from 2000 to 2020, given that existing conditions in the fishery sector and general economy persist into the future. The results appear to indicate that the Malaysian fishery sector may not be able to make significant contribution to the objectives above. Efforts need to be stepped up in order to increase fish production, reducing fish prices and increasing net value of fish trade.